Baseline intrinsic flammability of Earth’s ecosystems estimated from paleoatmospheric oxygen over the past 350 million years - Belcher,CM; Yearsley,JM; Hadden,RM; McElwain,JC; Rein,G (Proceedings of the National Academy of Sciences, 2010)
Atmospheric oxygen (O2) is estimated to have varied greatly throughout Earth’s history and has been capable of influencing wildfire activity wherever fuel and ignition sources were present. Fires consume huge quantities of biomass in all ecosystems and play an important role in biogeochemical cycles. This means that understanding the influence of O2 on past fire activity has far-reaching consequences for the evolution of life and Earth’s biodiversity over geological timescales. We have used a strong electrical ignition source to ignite smoldering fires, and we measured their self-sustaining propagation in atmospheres of different oxygen concentrations. These data have been used to build a model that we use to estimate the baseline intrinsic flammability of Earth’s ecosystems according to variations in O2 over the past 350 million years (Ma). Our aim is to highlight times in Earth’s history when fire has been capable of influencing the Earth system. We reveal that fire activity would be greatly suppressed below 18.5% O2, entirely switched off below 16% O2, and rapidly enhanced between 19–22% O2. We show that fire activity and, therefore, its influence on the Earth system would have been high during the Carboniferous (350–300 Ma) and Cretaceous (145–65 Ma) periods; intermediate in the Permian (299–251 Ma), Late Triassic (285–201 Ma), and Jurassic (201–145 Ma) periods; and surprisingly low to lacking in the Early–Middle Triassic period between 250–240 Ma. These baseline variations in Earth’s flammability must be factored into our understanding of past vegetation, biodiversity, evolution, and biogeochemical cycles.